Entrepreneurship in Birmingham and Manchester, 1851-1911: A Tale of Two Cities?. (1st September 2020) - Smith, Harry; Bennett, Robert J.; van Lieshout, Carry
ABSTRACT: It has long been argued that the economic structures of Birmingham and Manchester in the nineteenth century were fundamentally different, with Birmingham characterized by small workshops and high levels of social mobility and Manchester by factories and entrenched contrasts between workers and capitalists. This article uses new data to examine the reality of the economic structure of Birmingham and Manchester to see whether the assumptions of previous studies are borne out by the historical record. While it is true that Manchester had more large businesses than Birmingham in the period 1851–81, this view is a partial one. Manchester was home to a large number of small businesses, and both towns were complex economic units, with retail, commerce and services just as important as manufacturing to their economic life. This suggests that the traditional view of the economic basis of Birmingham and Manchester's politics requires amendment.